2000
DOI: 10.1007/s002100000226
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex hormones on vascular responses in the aorta of streptozotocin-diabetic male rats

Abstract: Diabetes mellitus reduces gender-related differences in the prevalence of cardiovascular disease by fading the vascular protective effects afforded by estrogen in females. However, the impact of estrogen treatment on and the contribution of androgens to vascular function in vessels from male diabetics are largely unknown. We investigated the effects of androgen deficiency and in vivo estrogen treatment by assessing the responsiveness to a number of vasoactive agents and the formation of eicosanoid mediators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…An increased contraction in cerebral arteries to endothelin and calcium ions but not phenylephrine and U46619 has also been reported [42] . Our results showing a decrease in contraction to phenylephrine in both male and female rats after 14 days of 17 ␤ -estradiol treatment is in line with other studies [5,43,44] .…”
Section: Discussionsupporting
confidence: 82%
“…An increased contraction in cerebral arteries to endothelin and calcium ions but not phenylephrine and U46619 has also been reported [42] . Our results showing a decrease in contraction to phenylephrine in both male and female rats after 14 days of 17 ␤ -estradiol treatment is in line with other studies [5,43,44] .…”
Section: Discussionsupporting
confidence: 82%
“…35 In those affected by diabetes mellitus and insulin resistance, vascular dysfunction has been associated with decreased endothelial NO production, higher oxidative stress and increased accumulation of advanced glycation end products and expression of receptor of advanced glycation end products. 36,37 Circulating advanced glycation end products disrupt cell-extracellular matrix and matrix-matrix interactions and increase collagen cross-linking, potentially leading to an increase in vascular stiffness. 38,39 Similar to glycemia, previous studies on lipid associations to vascular function have been equivocal, with some demonstrating baseline HDL and triglyceride values were associated with aortic stiffness, whereas others showed no association.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this assumption, it would be reasonable to think that hormone supplementation to restore the normal testosterone/estrogen ratio would be beneficial in women with type 2 diabetes with CVD complications. Indeed, a few studies have shown that hormone therapy in women with type 2 diabetes is associated with a reduction in visceral adiposity and improvement in lipid and glucose metabolism, all of which are risk factor of CVD 5860 . While the precise mechanisms by which sex hormones exert their effects and contribute to development of CVD are still being investigated, both clinical and experimental studies suggest that sex hormones are important regulators of fat, glucose and lipid metabolism, blood pressure, cardiovascular and renal function 5556, 6164 .…”
mentioning
confidence: 99%